Marvel-verse. Captain Marvel - DeConnick, Kelly Sue; Stohl, Margaret (Marvel Worldwide, Inc, 2020)
A collection of graphic novel stories following the adventures of Carol Danvers as Captain Marvel. Here Captain Marvel teams up with Spider-Man, learns more about her cat, Chewie, and encounters Kree legend Mar-Vell.